Kebijakan Penegakan Hukum Pidana dalam Penanggulangan Perjudian Online Ditinjau dari Undang-Undang Republik Indonesia No 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik - Muhammad Sahid; Drajat Wahyu Sasongko (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
This thesis Criminal Law Enforcement Policies in Combating Online Gambling in View of the Law of the Republic of Indonesia Number 19 of 2016 Concerning Information and Electronic Transactions. The rapid development of technology at this time is a great opportunity for criminals to commit crimes. The crime of gambling has now entered the world of the Internet, which is now known as online gambling. In reducing the crime rate of online gambling, it is necessary to know how law enforcement policies deal with online gambling crimes and what are the obstacles for law enforcement to tackle online gambling crimes. Writing this thesis uses the Normative Juridical Law Research method which is descriptive in nature so it does not intend to test hypotheses. There are two efforts to deal with online gambling, the first is preventive in nature, namely efforts to give appeals and carry out surveillance in cyberspace using Internet media. The second countermeasures are repressive, namely making arrests, processing, then filing to court and imposing criminal sanctions in accordance with Article 45 paragraph (2) of the ITE Law, Article 303 and Article 303 bis of the Criminal Code. Based on the results of this study, the authors provide suggestions: 1. It is necessary to increase law enforcement capabilities by upgrading knowledge of IT-based technologies. 2. It is hoped that law enforcers will be more progressive in eradicating online gambling crimes, in the case of online gambling, the authorities can massively block online gambling sites, by doing so, of course, this will minimize existing problems.